Solvability, Company Growth, and Voluntary Auditor Switching Impact on Audit Delay - Roharji, Febri; Dasmaran, Verliani; Masitoh, Masitoh (International Conference on Business Management and Accounting, 2023)
This study aims to determine the effect of Solvency and Company Growth on Switching Auditors and their impact on Audit Delay. This study uses secondary data with a population, namely manufacturing companies listed on the Indonesia Stock Exchange as many as 138 companies with an observation year of 2019-2021. The sampling technique used in this study is purposive sampling with multiple linear regression analysis methods for direct testing and Sobel test for indirect testing. The results of this study show that solvency does not have a significant influence on switching auditors, Company Growth does not have a significant influence on Switching Auditors, Solvency does not have a significant influence on Audit Delay, Company Growth has a significant influence on Audit Delay, Switching Auditors do not have a significant influence on Audit Delay, Switching Auditors are unable to mediate the effect of Solvency on Audit Delay and Switching Auditors are unable to mediate the effect of Company Growth on Audit Delay.